2011
DOI: 10.1007/s00404-011-1925-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 in women with persistence of DNA-HPV: a nested case–control study

Abstract: The present study suggests that IL-6 levels may be a marker of HPV DNA persistence, although further investigation is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Therefore, it is suggested that MBL may promote the rapid resolution of acute inflammation by increased production of IL‐6 as well as by the rapid clearance of foreign microbes and necrotic debris, which provoke acute inflammatory responses. On the other hand, MBL itself can help the clearance of infections agents and up‐regulate the production of IL‐6, promoting early termination of the acute inflammatory process and rapid transition to adaptive immune process …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, it is suggested that MBL may promote the rapid resolution of acute inflammation by increased production of IL‐6 as well as by the rapid clearance of foreign microbes and necrotic debris, which provoke acute inflammatory responses. On the other hand, MBL itself can help the clearance of infections agents and up‐regulate the production of IL‐6, promoting early termination of the acute inflammatory process and rapid transition to adaptive immune process …”
Section: Discussionmentioning
confidence: 99%
“…Possible effects of the results of IL ‐6 and Mannose‐binding lectin ( MBL )‐2 gene polymorphism and their products on Human papillomaviruses ( HPV ) infections …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…however, when activated, NFkB inhibits proliferation and immortalization (Vandermark et al, 2012). HPV persistence seems to be associated with low IL-6 levels (Rosa et al, 2012), and the rs5743836 polymorphism creates a novel IL-6-binding site, increasing the transcription and creating a loop of TLR9/IL-6 signalling amplification (Carvalho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%